The Effects of Rosemary (Rosemarinus Afficinalis) Pawder and Thyme (Thymus Vulgaris) Powder on Performance, Hematological, Biochemical Parameters of Male Quails - Ameen , Gulala .W.; AL-DALOE , Naz. N. SH; Noaman , H A (American Journal of Biology and Natural Sciences, 2025)
This study was conducted at the poultry farm of the Animal Production Department, College of Agriculture, University of Kirkuk, during the period from 02/25/2023 to 05/25/2023, to determine the effect of adding rosemary powder on the physiological and biochemical characteristics of blood and the antioxidant status in the blood serum of female quails. 64 male Japanese quails, eight weeks old, were used. The birds were randomly distributed into four treatments, each treatment containing four replicates, each replicate containing four male quails. They were then housed in battery cages, each cage consisting of 5 floors, each floor consisting of 3 cages, with four males inside each cage. The birds were fed ad libitum, and the treatments were distributed as follows: Treatment 1 was a control (no supplement), Treatment 2 added 0.50% rosemary powder, Treatment 3 added 0.50% thyme powder, and Treatment 4 added 0.50% rosemary powder + 0.50% thyme powder. The statistical analysis results showed that:There is a significant improvement in the levels of cholesterol TG -HDL LDL -VLDL, as well as URIC ACID-KREATINE and blood parameters by adding rosemary powder and thyme powder together or alone to the rations of male quails.